Ketamine for sedation in acutely painful procedures in Kenya: findings after implementation of the Every Second Matters-Ketamine package - Moytrayee Guha, MPH; Sebastian Suarez, DrMD; Moshood O Omotayo, PhD; Daniel I Sessler, MD; Khama Rogo, MD; Taha Yusufali, MD; Thomas F Burke, MD (Elsevier, 2019)
Background: Adequate pain management for painful procedures improves the quality and safety of patient care and has become accepted as a basic human right. In low-resource settings, pain relief for painful procedures is scarce because of cultural, attitudinal, legal, and system-related reasons, as well as a scarcity of anaesthetists. A practice of "hold still", where patients are forcibly held down during painful procedures, remains common in Kenya and in other low-resource settings. In December, 2013, we launched the Every Second Matters-Ketamine (ESM-Ketamine) package in Kenya, for use during emergency surgery when no anaesthetist is available. Here, we aim to describe how non-anaesthetists who were trained in an ESM-Ketamine programme broadened use of their skills to provide procedural sedation for patients in need of painful procedures when an anaesthetist would not have been previously called. Methods: Medical officers, nurses, and clinical officers in Kenya undertook a 5-day ESM-Ketamine competency-based training programme for non-anaesthetists. We provided every facility in the ESM-Ketamine initiative with wall charts, checklists, and kits. Trained providers recorded patients' demographic data, pre-operative diagnoses, the procedure or procedures undertaken, medications administered, and ketamine-related adverse events. Partners Healthcare and Maseno University gave ethical approval for the programme. Findings: Between Dec 1, 2013, and July 30, 2018, 62 ESM-Ketamine providers across 11 facilities administered ketamine to 512 patients undergoing painful procedures in non-training settings where an anaesthetist would previously not have been called. 273 patients (53·3%) were male and median age was 23 years (IQR 11-36 years). The five most common indications were: incision and drainage, debridement, or both (159 [31·1%]); fracture reduction (56 [10·9%]); circumcision (41 [8·0%]); wound repair (29 [5·7%]); and foreign body removal (26 [5·1%]). Median ketamine dose was 2·0 mg/kg (IQR 2·0 -3·0). Hallucinations or agitation treated with diazepam were reported in 45 patients [8·8%]; brief oxygen desaturation occurred in 22 (4·3%) patients. Prolonged (>30s) desaturations below 92% occurred in two patients (0·4%). The lowest desaturation was 85%. All patients recovered uneventfully. There were no deaths or injuries associated with ketamine use in the programme. Interpretation: The ESM-Ketamine package appears safe for use by trained providers in support of procedural sedation when previously an anaesthetist would not have been called. Scale-up of the ESM-Ketamine package may support the human rights imperative that every person deserves pain relief when undergoing a painful procedure. Funding: None.